Micro-networked metal coating using self-cracked WO3 inorganic thin film as sacrificial layer: Application to transparent flexible electrodes - Kim, Noeul; Kim, Youngho; Park, Jung Been; Cho, Hyeon Ho; Lee, Dong kyu; Kwak, Geonho; Yu, Hak Ki (Thin Solid Films, 2021)
A method of fabricating a micro-networked metal electrode using a self-cracking WO3 oxide thin film as a sacrificial layer is presented. The width of the formed crack can be adjusted to a size of 10 to 40 µm by adjusting the wet-etching time in dilute NaOH solution, and accordingly, the electrical conductivity and transmittance of the electrode can be adjusted. An electrical conductivity of approximately 100 Ω/sq was measured at an average transmittance of 95.6% in the visible light region, and when applied to a flexible substrate, the electrical resistance was maintained stable even with repeated bending tests. The method proposed in this study can be applied to various transparent flexible electrode devices.
Keywords: Electrical conductivity; Etching time; Flexible electrodes; Inorganic thin films; Metal electrodes; Metal grid; Oxide thin films; Sacrificial layer; Self-cracked; Transparent flexible electrode; Metal grid; Self-cracked; Transparent flexible electrode